Targeting DNA‐Dependent Protein Kinase for Cancer Therapy. (29th May 2017) - Harnor, Suzannah J.; Brennan, Alfie; Cano, Céline
Abstract: The catalytic activity of DNA‐dependent protein kinase (DNA‐PK) is critical to its ability to repair lethal DNA double‐strand breaks (DSBs). This includes repair of DSB lesions resulting from oxidative stress, oncogene‐induced transcription, or following therapeutic treatment of cancer cells. Armed with this knowledge, many attempts have been made to identify small‐molecule inhibitors of DNA‐PK activity as an approach to induce tumour chemo‐ and radiosensitisation. This review examines the structures of known reversible and irreversible inhibitors, including those based on chromen‐4‐one, arylmorpholine, and benzaldehyde scaffolds. DNA‐PK catalytic inhibitors, such as VX‐984 (8‐[(1 S )‐2‐[[6‐(4, 6‐dideuterio‐2‐methylpyrimidin‐5‐yl)pyrimidin‐4‐yl]amino]‐1‐methylethyl]quinoline‐4‐carboxamide) and M3814 (( S )‐[2‐chloro‐4‐fluoro‐5‐(7‐morpholinoquinazolin‐4‐yl)phenyl]‐(6‐methoxypyridazin‐3‐yl)methanol), have now progressed into clinical development which should help to further advance our understanding of whether this approach is a promising therapeutic strategy for the treatment of cancer. Abstract : Stopping the fixer : The catalytic activity of DNA‐dependent protein kinase (DNA‐PK) is critical to its ability to repair lethal DNA double‐strand breaks, and many attempts have been made to identify small‐molecule inhibitors of DNA‐PK activity as an approach to induce tumour chemo‐ and radiosensitisation. DNA‐PK catalytic inhibitors have now progressed into clinical development, which should help to further advance our understanding of whether this approach is a promising therapeutic strategy for the treatment of cancer.